An Empirical Study on the Change of Consumption Level of Chinese Residents - Wenxing Wang; Xiangdan Wen (International Journal of Engineering and Management Research, 2020)
With the rapid development of Chinese economy since the reform and opening up, people's living standards have been improved, and people's consumption level has been gradually improved. Consumption plays an important role in stimulating economic growth. At present, China needs to adjust its economic structure and optimize its industrial structure. Therefore, it is very important to analyze the factors that affect the consumption level of Chinese residents and study the main factors for promoting the healthy and sustainable development of Chinese economy. Therefore, based on the statistical data from 1995 to 2018, this paper collects the variable data that affects the consumption level of residents, such as the freight volume of infrastructure railway and highway, the per capita disposable income of national residents, ordinary college students, the consumer price index of residents, the average real wage index and the gross domestic product. And through the establishment of multiple linear regression model and the stepwise regression, the paper also finds out the main factors influencing the consumption level of residents. Using R language and analyzing the results of the research, we can draw the conclusion that the national per capita disposable income, ordinary college students and consumer price index and GDP are the main factors that affect the consumption level of Chine.